The Use of Graphic Organizer Strategies to Improve Students' Writing Skills in English Language Teaching - Muhammad Labib Al Halim (SAGA: Journal of English Language Teaching and Applied Linguistics, 2024)
This research is motivated by the weak ability of students' writing in learning English. This research was conducted with the aim of improving English language skills, especially writing skills through the use of the graphic organizer strategy. This research was conducted on first semester students at Billfath Lamongan University. The subjects of this research were students of the English program from several research programs totaling 34 students. This research uses a Classroom Action Research design by Kemmis and Mc Taggart model in four stages, namely planning, implementing action, observing, and reflecting. The results of the preliminary test showed that students' writing skills were still low. The results of the assessment on the practice of writing texts using the assessment rubric show that there are still many students who have not reached the mark according to the criteria. The percentage of scores obtained by students are dominated by the "poor" criterion with 41%, fair 32%, good 18%, very poor 9%, and excellent 0%. While, the students' competence increased and has reached the specified minimum completeness criteria in the final test. The percentage of scores obtained by students are dominated by the "good" criterion with 50%, excellent 32%, fair 18%, poor 0%, and very poor 0%. The results of this research prove that the use of the graphic organizer strategy significantly improves students' writing skills and also has a positive impact on students' attitudes toward learning English.